The implementation of scaffolding technique to improve students’ writing skill - Ardillah Kurais; Bangun Hutama Wardana (EKSPOSE, 2021)
Scaffolding is a technique that help the students to improve their ability by giving them aids or supports through five basic steps of this technique consisted of intentionality, appropriatenes, structure, collaboration and internalization. The scaffolding technique was applied in order to improve the students’ ability in writing skill. This study was conducted on the fifth semester students of IAIN Palopo by applying classroom action research. The data and the source data of this study was all of the students in English department. The result of this study showed that there increasing points from cycle I and the cycle II. The first cycle showed that two students obtained good score (13.3%) and 14 students obtained poor score (86.7%) which the mean score was 61.8. in the second cycle there was a development wherein 10 students obtained good score (66.7%) and five students where in fair score (33.3%) which the mean score was 75. The difference between two cycles was on the improvement of given support or appropriate scaffolding to the students. The five steps of scaffolding technique did not mean to help students from the beginning until finishing the works but to give them a guidance where the certain parts still have difficulty to solve.